Nuclear and isotopic techniques for the characterization of submarine groundwater discharge in coastal zones : results of a coordinated research project 2001-2006. (IAEA-TECDOC, 2008)
In 2000, the IAEA and UNESCO jointly developed an initiative to assess methodologies and the environmental importance of submarine groundwater discharge (SGD) for coastal zone management. Under that mandate, a coordinated research project was commissioned to test the application of recently developed nuclear and isotopic techniques suitable for quantitative estimation of various components of SGD. This publication highlights several methods of SGD assessment, carried out during a series of five intercomparison experiments in different hydrogeologic environments. It reviews the scientific and management significance of SGD as well as measurement approaches, and presents the results of the intercomparison experiments.--Publisher's description.